Gordon Research Conference on Scientific Information Problems in Research, 1974 - Gordon Research Conferences (1974)
Group photograph of attendees at the Gordon Research Conference on Scientific Information Problems in Research held at Colby College in New London, New Hampshire in July 1974.
Keywords: Gordon Research Conferences; Portraits, Group; Congresses and conventions